Service: the new focus in international manufacturing and trade - Peters, Hans Jurgen (IBRD Washington, D.C.US, 1992)
Reports on the findings of a survey of 1,450 businesses engaged in manufacturing, wholesaling and retailing and various aspects of the service industries, focusing on the transport warehousing and information processing industries.